On the debate over issues of language culture in Hungary (Philology, 2024)
The paper presents and comments on different opinions and views on the activity of cultivating the Hungarian standard language, also with regard to the relationship between linguistics and speech culture in the Hungarian linguistic and educational tradition. Disagreements over the place of language culture in linguistic research, the role of linguists in language cultivation, the cult of the exemplary standard language, the evaluation of linguistic innovations, the unity of the literary-linguistic norm across the entire Hungarian linguistic territory, etc. reveal the complexity and intricacy of the issues related to language culture activity and codification practice, as well as the influence of political, ideological and cultural-historical factors. These discussion questions shed light on current problems concerning changes in the speech practice of the contemporary Hungarian language community, the state of the Hungarian national language and literary-linguistic norms, the need to introduce new methods and techniques into the education system, etc. in order to conduct an adequate and effective language policy. The success of the country’s overall language strategy depends on the correct formulation and solution of the outlined problems.
Keywords: contemporary Hungarian language; language culture; language cultivation; speech behaviour; linguistics and language culture